NIETZSCHE'S POLITICAL THOUGHT- SEARH FOR GREATNESS ACCORDING TO GREEK VALUES (Heritage, 2024)
The aim of the paper is to prove that Nietzsche's political thought is based on ancient values ​​that are a model for creating the future. They are suppressed by "adjustments" since modern politics rests on the delusion of social norms and imposed new ideologies that it is possible to establish universal agreement and justice. It is necessary to reevaluate values ​​through manifestations of the will for power and greatness of the human being. Nietzsche advocates a policy based on the improvement of humanity and a true philosophy with noble values, a healthy culture, and an affirmation of life. The will to power is the foundation of Nietzsche's philosophy of politics and the formulation of political thought anticipated through his concept of "great politics", led by an elite class of philosopher-legislators who will create new values ​​and inspire future generations to transform into good Europeans.
Keywords: agon, will to power, free spirits, revaluation of values,